Carbon dioxide biofixation by Chlorella vulgaris at different CO2 concentrations and light intensities. Issue 5 (26th May 2014) - Clément‐Larosière, Barbara; Lopes, Filipa; Gonçalves, Ana; Taidi, Behnam; Benedetti, Marc; Minier, Michel; Pareau, Dominique
<x xml:space="preserve">Abstract</x> In order to develop an effective CO2 mitigation process using microalgae for potential industrial application, the growth and physiological activity of Chlorella vulgaris in photobioreactor cultures were studied. C. vulgaris was grown at two CO2 concentrations (2 and 13% of CO2 v/v) and at three incident light intensities (50, 120 and 180 μmol m−2 s−1) for 9 days. The measured specific growth rate was similar under all conditions tested but an increase in light intensity and CO2 concentration affected the biomass and cell concentrations. Although carbon limitation was observed at 2% CO2, similar cellular composition was measured in both conditions. Light limitation induced a net change in the growth behavior of C. vulgaris. Nitrogen limitation seemed to decrease the nitrogen quota of the cells and rise the intracellular carbon:nitrogen ratio. Exopolysaccharide production per cell appeared to be affected by light intensity. In order to avoid underestimation of the CO2 biofixation rate of the microalgae, exopolysaccharide production was taken into account. The maximum CO2 removal rate (0.98 g CO2 L−1 d−1) and the highest biomass concentration (4.14 g DW L−1) were determined at 13% (v/v) CO2 and 180 μmol m−2 s−1. Our results show that C. vulgaris has a real potential for industrial CO2 remediation.